Targeting climate finance for global forests - Kemen G. Austin; Alice Favero; Nicklas Forsell; Brent L. Sohngen; Chris M. Wade; Sara B. Ohrel; Shaun Ragnauth (Nature Communications)
Abstract Comprehensive data on costs of mitigation are needed to guide the scale and distribution of climate finance to sectors and regions where it will be most cost effective. We estimate the finance required to meet regional forest-based mitigation targets, aggregated from Nationally Determined Contributions (NDCs). Regions accounting for 70% of global forest carbon can meet their forest-based NDCs with carbon prices below $100/tonne CO2. The total investment required to meet regional targets is $20-72 billion per year by 2030. Under a global coordination scenario, in which the same level of finance is available, but mitigation takes place where it is least costly, we project twice as much mitigation in 2030 as in the upper bound NDC scenario, at the same cost. This highlights potential cost savings from increasing mitigation in regions with low-cost mitigation potential that is not reflected in current national commitments and informs the next generation of NDCs.